Evaluación y análisis de los planes de gestión integral de residuos hospitalarios y similares (PGIRH) de los hospitales de la red adscrita (E.S.E.) (2005)
Hospital waste management plans are a fundamental part of the management that a hospital must carry out in favor of the environment and human health. Poorly managed hospital waste generates a potential risk for all personnel involved with it, from the physician to the collector who carries out the final disposal. The plans should be evaluated and monitored by the institution itself and by the entity responsible for the surveillance and control of these institutions. In Bogota, the District Secretary of Health is in charge of this task. In order to evaluate and analyze the management plans and indicators, checklists were implemented to verify whether or not the generating entities are complying with the regulations governing the management of hospital waste. For this work, the sample was taken from the hospitals of the network attached to the District Secretary of Health (ESE)1. It is clear that health care providers are not complying with the regulations because only 29.8% of the total number of providers that generate hazardous waste have sent their hospital waste management plan (PGIRH) to the Secretary of Health or have been verified during visits by the SDS2. This means that the SDS must implement a monitoring and control system, the objective of which is based on guiding the providers so that they can correctly prepare their management.